Resource management of offshore units construction operations in multi-project environment - Rajpurohit Dharmpal Singh (2014)
To stay competitive in the booming rig-building industry and era, world leading rigdesigner and builder like Keppel Offshore and Marine endeavors to manage the construction resource in a scientific way to cut cost and improve operation efficiency. Although a leader in operation and manufacturing excellence, it is eager to exploit room for management improvement in the areas of painting operation resource, scaffolding resource and manpower resource.